Analisis Faktor-Faktor yang Mempengaruhi Kinerja Keuangan Sektor Perbankan di Bursa Efek Indonesia - Uli, Evita; Siyo, Kasim (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
The purpose of this study is to determine the partial to simultaneous influence of Capital, Asset, Management, Earnings, Liquidity variables as well as sensitivity to market risk on Return on Assets (ROA). This research was conducted on Banking Sector companies listed on the Indonesia Stock Exchange. The research approach uses quantitative research. The total population in this study is 46 banking companies that have entered and listed stocks during the observation period of 2018-2022, which is 5 years. The company met the sample withdrawal criteria, namely the entire population of 40 companies, so the sample in this study was 40 x 5 = 200 financial statements. The analysis tool in this study is Eviews version 13. The data analysis technique uses panel data regression analysis. The results of his research show that partially CAR has a significant positive effect on ROA. NPLs have no positive and insignificant effect on ROA. LDR has a significant positive effect on ROA. BOPO has a significant positive effect on ROA. PDN had a significant positive effect on ROA and NPM had no positive and insignificant effect on ROA. Meanwhile, simultaneously the variables CAR, NPL, LDR, BOPO, PDN and NPM simultaneously had a significant positive influence on ROA. The contribution of all variables was 53.30%.